Analisis Semiotika Representasi Toleransi Beragama Dalam Film Pendek ”Berdoa, Mulai” Di Channel Youtube Degradians Studio - Anisa Santiawan (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study aims to analyze the representation of religious tolerance in the short film "Berdoa, Mulai" Religious differences in Indonesian society demand mutual respect to create a harmonious life. However, in practice, tolerance is not always optimal, especially in social settings such as schools. This study used a qualitative method with Roland Barthes's semiotic approach, analyzing denotative and connotative meanings. Data were obtained through observation and documentation of scenes, dialogue, and symbols in the film. The results show that religious tolerance is represented through social interactions such as mutual respect, a sense of belonging, and the individual's ability to adapt to diverse environments. The main character, as a minority group, is able to interact with the majority without losing their identity. However, the film also shows that tolerance is not yet fully ideal, as majority dominance and differing views persist in everyday life.